PERAN REPORTER DALAM PROSES PRODUKSI BERITA DI DAAI TV BIRO MEDAN - Syifa Nadia Humaira; Sori Monang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Television is still the main public means of accessing information in its audio-visual format. DAAI TV is a private television station owned by the Tzu Chi Buddhist humanitarian foundation with the motto truth, virtue and beauty. All levels of management and reporters carry a moral responsibility for every program they produce. The purpose of this study was to find out how the role of reporters during the news production process at DAAI TV Medan Bureau.This study used a qualitative method by interviewing two reporters and an assistant for the Sumatra Frame news program. The results of the study show how the role of the Medan bureau DAAI TV reporter in the news production process through four broadcast media management functions, namely the planning stage, namely at this stage the role of the reporter is to find and determine news coverage material, the organizing stage (organizing) namely dividing the coverage theme, the implementation stage (directing) is executing what has been designed in the pre-production stage together with the cameraman, and the control stage is making scripts and coordinating with the editor to produce news coverage that is airworthy.